Strengthening Research-Education-Extension (R-E-E) Linkage in New Context of Federal Structured Nepal - Mahesh Jaishi (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2020)
Objective: The objective of this paper to examine the major limitations of past efforts in Nepal regarding the link between agriculture research, education, and extension and to highlight the government's strategy and policy measures to overcome these limitations in the new federal structure in Nepal.   Methodology: The paper is based on the government policy paper, articles, books, reports, and website. Policymakers, faculties, and researchers from three major stakeholders of REE blended through key informant interviews.  Result:  Paper concluded that linkages between the research, education, and service delivery are the weakest. Lack of extension policy, lack of joint ventures or common programs, no functional link between universities, agricultural ministry, research institute, and private sector in policy forums are weakening REE linkages. Rural extension and community development can be developed as a three-way partnership. i) land-grant university/college in each state including municipalities, ii) state government through ministry and department iii) local government through municipalities, and Community Agriculture Extension Service Centers (CAESC).   Implication: A typological model is suggested to explain organizational and operational linkage strategies. Taking these together, the scattered efforts and services being provided by the existing structure, Agriculture Academic Institution (AAI) should able to fulfill these gaps with the close collaboration of community initiative as suggested by Agriculture Development Strategy (ADS). While doing so, the existing institutional structure can also be restructured and revitalized.